Materiales para obturación en pulpectomías en dentición primaria. revisión sistemática - Moreta Criollo, Johanna Estefanía (2024)
Introduction: The success of pulp therapies lies in conserving the tooth to avoid aesthetic and functional alterations in the permanent dentition. The choice of high-quality materials is crucial in this process. Therefore, it is essential to know the advantages and disadvantages of options such as Vitapex, Metapex, ZOE, and Endoflas, as each has a unique composition, resulting in different outcomes. Objective: to determine the level of efficacy of obturation materials in pulpectomies of primary teeth. Method: the information was obtained through databases such as PubMed, Scielo, and Redalyc, using search lines and MeSH terms. Based on inclusion and exclusion criteria and the PRISMA methodology, a total of 31 articles were selected and only 14 were included for review and discussion in the present review. Results: The final findings of each study regarding the materials Endoflas, ZOE, Metapex, and Vitapex were analyzed, categorizing them according to the level of efficiency based on various parameters such as chemical composition, postoperative sequelae, and functional stability, establishing the one with the best conditions. Conclusion: The reviewed obturation materials, all have beneficial properties, but Metapex and Vitapex show a deficient ability to remain within the canal, ZOE is not recommended for teeth close to exfoliation, and Endoflas does not present the previous disadvantages, being the most suitable for endodontic procedures in children.